1983
DOI: 10.1115/1.3240956
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Fluctuations on the Surface of Two Circular Cylinders in Tandem Arrangement

Abstract: The fluctuating pressures on the surface of two circular cylinders of the same diameter in tandem arrangement were measured in the upper subcritical regime to obtain the distributions of their rms values and the spanwise and circumferential correlations. These pressures were subsequently integrated to yield the spanwise correlation length and the rms values of fluctuating lift and drag as functions of the spacing between the two cylinders. The rms lift and drag were much larger for the downstream cylinder than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 0 publications
9
37
0
Order By: Relevance
“…Measurements have been made for base pressure, interference force coefficients, lift and drag forces, and Strouhal numbers for different arrangements (Hor 1959;Mair and Maull 1971;Zdravkovich 1977;Kiya et al 1980;Arie et al 1983;and Dayoub 1982).…”
Section: Two Cylinders In Staggered Arrangementmentioning
confidence: 99%
“…Measurements have been made for base pressure, interference force coefficients, lift and drag forces, and Strouhal numbers for different arrangements (Hor 1959;Mair and Maull 1971;Zdravkovich 1977;Kiya et al 1980;Arie et al 1983;and Dayoub 1982).…”
Section: Two Cylinders In Staggered Arrangementmentioning
confidence: 99%
“…The situation where the cylinders are aligned to the flow direction ͑the so-called tandem arrangement͒ has been of particular interest and a critical spacing ͑around 3.8 cylinder diameters͒ has long been detected by Ishigai et al 3 This feature has since been confirmed in high Reynolds number flows. [4][5][6] To our knowledge, the only low Reynolds number experiments of Tanida et al 7 shows a discontinuity in the drag coefficient curve for a spacing around of 3.9 diameters. These results were further confirmed by Ohmi and Imaichi 8 and by the recent numerical simulations of Meneghini et al 9 and Sharman et al 10 To our knowledge, the most complete description of the tandem cylinder wake at low Reynolds numbers was recently given by Mizushima and Suehiro.…”
Section: Introductionmentioning
confidence: 99%
“…In Comparison with the two cases, it is clearly observed that the pressure drag for the second case (grooved-grooved) is reduced and this for the Reynolds number Re 2 = 5×10 4 and Re 3 = 7×10 4 . This remark is in agreement with Ladjedel et al [16] in their experimental investigation.…”
Section: Fig1 Experimental Set Upmentioning
confidence: 97%
“…Arie et al [3] pointed out that fluctuation in drag force acting on both cylinders is weakly dependent on spacing. On the other hand, Igarashi [4] reported that the fluctuation in pressure associated with fluctuation in lift and drag forces acting on a downstream cylinder is strongly dependent on spacing between the cylinders. Moreover, some discrepant points among various studies can be found in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation